Presence and Physiologic Function of the Renin–Angiotensin System in Mouse Lacrimal Gland - Yaguchi, Saori; Ogawa, Yoko; Shimmura, Shigeto; Hatou, Shin; Nakamura, Shigeru; Inaba, Takaaki; Imada, Toshihiro; Ozawa, Yoko; Kawakami, Yutaka; Ishida, Susumu; Tsubota, Kazuo (Investigative ophthalmology & visual science, 2012)
To investigate the expression, localization, and physiologic function of renin-angiotensin system (RAS) components in the mouse lacrimal gland. Lacrimal glands and cultured lacrimal gland fibroblasts from wild-type (WT) BALB/c (H-2(d)) mice were used. Reverse transcription-polymerase chain reaction (RT-PCR) and immunohistochemistry were used to determine the expression and localization of the RAS components, prorenin/renin, angiotensin-converting enzyme (ACE), angiotensin II, angiotensin II type 1 receptor (AT1R), and angiotensin II type 2 receptor (AT2R) in the normal mouse lacrimal gland. To examine the change in tear secretion, mice received ARB (AT1R blocker) or AT2R antagonist. Tear secretion was assessed by cotton thread test before and after drug administration. The mRNAs coding for angiotensinogen, prorenin, ACE, and both AT1R and AT2R were found in normal lacrimal gland tissue and cultured lacrimal gland fibroblasts. Prorenin/renin and ACE were identified in myoepithelial cells around ducts and acini and in blood vessels. Angiotensin II, AT1R, and AT2R were observed in the ducts and interstitial fibroblasts. AT1R and AT2R were also localized in blood vessels. All the cultured lacrimal gland fibroblasts expressed angiotensin II, AT1R, and AT2R. Tear secretion increased in mice that received ARB. The results are consistent with the hypothesis that a tissue-specific RAS is present in the lacrimal gland, and suggest that fibroblasts are one of the cell types playing a role in the tissue RAS. Tissue RAS might be involved in tissue function of regulating tear secretion in the lacrimal gland.